2023
DOI: 10.1002/adfm.202300049
|View full text |Cite
|
Sign up to set email alerts
|

J‐Type Self‐Assembled Supramolecular Polymers for High‐Performance and Fast‐Response n‐Type Organic Electrochemical Transistors

Abstract: To date, high-performance organic electrochemical transistors (OECTs) are almost all based on conjugated polymers. Small molecules can be synthesized with high purity without batch-to-batch variations. However, small molecules require highly crystalline films and good molecular packings to achieve high charge carrier mobilities. Such features make their films unsuitable for ion diffusion or make their molecular packing distorted due to ion diffusion, resulting in poor ion/charge carrier transport properties an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Recently, Lei et al reported two small molecules with the TDPP as the building block and two electron-deficient malononitrile (CN) and RD as the end functional groups. 33 TDPP-RD-G7 (Fig. 5c) was capable of forming J-type supramolecular polymers and ''polymer-like'' networks, which can enhance its charge transport and reduce its susceptibility to ion diffusion.…”
Section: Bti Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lei et al reported two small molecules with the TDPP as the building block and two electron-deficient malononitrile (CN) and RD as the end functional groups. 33 TDPP-RD-G7 (Fig. 5c) was capable of forming J-type supramolecular polymers and ''polymer-like'' networks, which can enhance its charge transport and reduce its susceptibility to ion diffusion.…”
Section: Bti Derivativesmentioning
confidence: 99%
“…These advancements include the development of a no-side-chain polymer BBL, the introduction of conductive polymer PBFDO, 31 the proposal of “doped state engineering”, 14 and the use of small molecule materials. 32,33 Among these materials, PBFDO has shown impressive performance. 31 However, PBFDO possesses a hydrophobic backbone with no hydrophilic side chains and it only shows good performance in thin films (∼50 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Pure p-type redox polymers bear, for example, triarylamine or carbazole redox units. 4 On the small molecules front, the films of oligoether tethered fullerenes, 5 thiophene-flanked diketopyrrolopyrrole units, 6 polycyclic systems consisting of naphthalene bis-isatin dimer core with rhodanine terminals, 7 or thiophene-EDOT based cores 8 are among the structures that can be electrochemically doped and de-doped in aqueous media, while they are yet to be commonly used by different research teams. All these systems can be modified with additives, dopants, and through processing and post-processing.…”
Section: The Materials – Search For Model Systemsmentioning
confidence: 99%
“…The organic thin-film transistors (OTFTs) have attracted great attentions for their inherent advantages on the low-cost, low-temperature manufacture, solution processable, and good mechanical flexibility, and their widely application prospects in the fields of flat panel displays, integrated circuits (ICs), memories, and sensors [1][2][3][4][5]. In past two decades, tremendous efforts have been devoted to develop the OTFTs, for promoting the commercialization.…”
Section: Introductionmentioning
confidence: 99%